The Effect of Wordwall Learning Media on Arabic Mufrodat Mastery in Grade III Students at Madrasah Ibtidaiyyah Negeri II - Khotijah, Siti; Hidayat, Ahmad Fadhel Syakir; Nisyam, Badrun; Khair, Miftahul; Muhamad, Mar'ie (Borneo Journal of Language and Education, 2022)
This study aims to determine the mastery of students' mufrodat before and after the application of wordwall media and to determine the effect of wordwall media on the mastery of students' mufrodat in class III MIN 2 Samarinda. The research method used in this study is a quasi-experimental study with a non-equivalent control group design model. The results of the study were 1) The mastery of students' mufrodat before the application of wordwall media in the control class and the experimental class was very low. 2) Students' mastery of mufrodat after the application of wordwall media increased very significantly. 3) The influence of wordwall media on students' mastery of mufrodat is known by conducting several tests, namely to determine the direction and magnitude of the influence of wordwall media on students' mastery of mufrodat, researchers conducted a correlation test. Based on the results of the correlation test, obtained the value of sig. The 2-tailed value is 0.00 < 0.05 and the Pearson correlation value is 0.886 which indicates that there is a very strong relationship with students' mastery of mufrodat. To test the hypothesis, the researcher used the paired sample t test, while the sig. 2-tailed obtained is 0.00 <0.05, this indicates that there is an influence of wordwall media on students' mastery of mufrodat. And the results of the determination test of 0.779 showed that wordwall media had an effect of 77.9% on students' mastery of mufrodat.